Analysis of System and Procedures for Providing Goods and Services at PT Traktor Nusantara Medan Branch - Nafinkan, Natasya Nabila; Wira, Teguh Satya (SEIKO : Journal of Management & Business, 2024)
The purpose of this research is to understand the procurement system and procedures at PT Traktor Nusantara Branch Medan. The method used in this research involves reading, interviews, and qualitative descriptive analysis. The procurement system for goods and services involves two methods: cash before delivery and cash after delivery. The procedures for procuring goods and services include several stages: placing orders, making payments, and distribusing goods and services to customers.